Machining process of spiral grinding wheel

By optimizing the resin material ratio and using high-temperature and high-pressure curing method for bonding, combined with mold extrusion and fine grinding processes, the shortcomings of spiral grinding wheels in terms of wear resistance and service life are solved, and higher wear resistance and high temperature resistance are achieved, extending the service cycle and improving working efficiency.

CN119820492APending Publication Date: 2025-04-15ZHENGZHOU QISHENG MACHINERY EQUIP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510263464.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing spiral grinding wheels have shortcomings in wear resistance and service life, especially in high temperature environments, traditional resin materials are prone to softening, deforming or failing, resulting in the peeling of the grinding bar or the working efficiency decrease.

Method used

By optimizing the ratio of epoxy resin, polyurethane resin and nanofiller, a high-temperature fluid state resin material is prepared, and a mold extrusion is used to form a grinding strip. The bonding is performed using high-temperature and high-pressure curing method, and the outer side of the grinding strip is finely polished to control the surface roughness between Ra0.5 and Ra1.5.

Benefits of technology

It achieves higher wear resistance and high temperature resistance, improves the stability and service life of resin materials during high-speed grinding, extends the service cycle of spiral grinding wheels and improves working efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119820492A_ABST
    Figure CN119820492A_ABST
Patent Text Reader

Abstract

The invention relates to the field of spiral grinding wheels, and discloses a spiral grinding wheel machining technology which comprises the following steps that S1, a base body is machined; s2, preparing a resin material; s3, a mold is used for extruding the resin material, and a grinding strip is obtained; s4, the grinding strip is bonded to the base body, and a complete spiral grinding wheel structure is formed; s5, the outer side faces of the bonded grinding strips are ground; the resin material in the step S2 comprises the following components: 60%-80% of epoxy resin; 20% to 40% of polyurethane resin; 10% to 20% of nano boron nitride; 5%-15% of nano silicon carbide; 5% to 15% of aluminum nitride; and 1%-3% of a surface reinforcing agent. By optimizing the proportion, higher wear resistance and high temperature resistance are achieved, the stability of the resin material in the high-speed grinding process is improved, the service life of the resin material in the high-speed grinding process is prolonged, and longer service cycle and higher working efficiency are provided for the spiral grinding wheel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of spiral grinding wheels, in particular to a processing technology of spiral grinding wheels. Background Art

[0002] The spiral grinding wheel is a highly efficient abrasive tool specially designed for grinding the surface of workpieces. Its working principle is to remove the material on the surface of the workpiece through the rotation of the grinding wheel and the cutting action of the abrasive, thereby achieving grinding, finishing or roughing of the workpiece.

[0003] Spiral grinding wheels are widely used in the fields of metal processing and tool manufacturing, especially in the production of high-precision grinding and cutting tools. The performance of the grinding wheel directly affects the processing quality and production efficiency of the workpiece. The spiral grinding wheel in the prior art is mainly formed by bonding the grinding strip to the substrate to form an integral structure, and then grinding the surface to achieve the expected cutting performance. However, in practical applications, these traditional processes still have some significant technical deficiencies, which affect the stability and service life of the grinding wheel.

[0004] First, in the prior art, although attempts have been made to improve wear resistance by increasing the proportion of fillers or improving the resin formula, these methods often have problems such as uneven filler dispersion and unstable material properties. Especially in high temperature environments, traditional resin materials are prone to softening, deformation, or even failure, resulting in the shedding of grinding wheel strips or reduced work efficiency.

[0005] Secondly, the limitation of the bonding process is one of the main reasons for the unstable performance of the grinding wheel. Traditional grinding strip bonding methods mostly use epoxy resins or other adhesives that cure at room temperature or low temperature. This type of process lacks precise control of temperature and time during the curing process, resulting in uneven bonding strength. Under high-speed grinding or high-load working environments, the bonding layer is prone to cracking or falling off due to insufficient strength, which in turn causes the grinding wheel to fail. The shedding of grinding strips will not only shorten the service life of the grinding wheel, but may also damage the workpiece during processing and reduce processing efficiency. In addition, due to weak bonding, the grinding wheel may vibrate during operation, further affecting the grinding accuracy and the quality of the workpiece surface. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a processing technology for a spiral grinding wheel, which solves the problems of poor wear resistance and insufficient service life of the prior spiral grinding wheel.

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: A processing technology for a spiral grinding wheel comprises the following steps: S1, processing the substrate; S2, preparing resin material; S3, using a mold to extrude the resin material to obtain a grinding strip; S4, bonding the grinding strip to the substrate to form a complete spiral grinding wheel structure; S5. Grind the outer side of the bonded grinding strip.

[0008] Preferably, the resin material in step S2 includes the following components: Epoxy resin: 60% to 80%; Polyurethane resin: 20% to 40%; Nano boron nitride: 10% to 20%; Nano silicon carbide: 5% to 15%; Aluminum nitride: 5% to 15%; Surface enhancer: 1% to 3%; Wherein, the surface enhancing agent includes a silane coupling agent or a titanate coupling agent.

[0009] Preferably, the epoxy resin is bisphenol A epoxy resin, and its molecular weight ranges from 400 to 600.

[0010] Preferably, the polyurethane resin is a thermosetting polyurethane resin with a molecular weight ranging from 1000 to 3000.

[0011] Preferably, the preparation in step S2 includes: S21, mixing epoxy resin and polyurethane resin in a ratio of 60% to 80% and 20% to 40%, using mechanical stirring to evenly mix, the stirring speed is 300 rpm to 600 rpm, and the stirring is continued for 30 minutes to 1 hour; S22, adding nano boron nitride, nano silicon carbide and aluminum nitride into the resin matrix in proportions of 10% to 20%, 5% to 15% and 5% to 15%, respectively, and uniformly dispersing them by high shear mixing; S23, adding a surface enhancer in a ratio of 1% to 3%, and continuing stirring for 10 to 15 minutes to allow the enhancer to react with the resin matrix to obtain a high-temperature fluid state resin material; S24, the high temperature fluid state resin material enters step S3.

[0012] Preferably, in the step S1, the substrate is a light alloy material, and the light alloy material includes aluminum alloy, magnesium alloy, aluminum-magnesium alloy and alloy combinations thereof.

[0013] Preferably, the grinding strips in step S4 are bonded using one or more of epoxy resin or polyurethane adhesive.

[0014] Preferably, in the step S5, a grinding wheel is used to grind the outer side of the grinding strip, and the symmetrical grinding angle accuracy is controlled within ±0.05° to ±0.1°, the grinding feed speed is 0.1mm / s to 0.3mm / s, and the grinding wheel particle size is 60 mesh to 100 mesh.

[0015] Preferably, the extrusion feed speed of the resin material in step S3 is 0.1 mm / s to 0.5 mm / s, and the extrusion pressure is 0.5 MPa to 2 MPa. After the resin material in the mold is filled into the desired shape, it is naturally cooled for 1 to 2 hours to obtain the desired grinding strip.

[0016] Preferably, in step S4, the bonding is performed using a high temperature and high pressure curing method, the curing temperature is controlled at 50° C. to 80° C., and the curing time is 1 hour to 2 hours.

[0017] The present invention provides a processing technology for a spiral grinding wheel, which has the following beneficial effects: 1. By optimizing the ratio of epoxy resin, polyurethane resin and nanofiller, higher wear resistance and high temperature resistance are achieved. This technical solution improves the stability and service life of the resin material during high-speed grinding. Compared with the formula in the existing technology, it further optimizes the performance of the material, making it perform better in high-load and high-temperature working environments, providing a longer service life and higher working efficiency for the spiral grinding wheel.

[0018] 2. The bonding process of the present invention adopts a high temperature and high pressure curing method, so that the bonding strength between the grinding strip and the substrate is optimized. Compared with the traditional bonding method, the curing temperature and time control of the present invention are more precise, thereby avoiding the problem of grinding wheel grinding strip falling off or failure due to loose bonding, and enhancing the overall structural stability and service life of the grinding wheel.

[0019] 3. The present invention controls the surface roughness of the grinding bar to ensure that it is between Ra0.5 and Ra1.5. This technology can effectively improve the cutting performance of the grinding wheel and reduce the occurrence of surface unevenness and thermal damage. Compared with the existing process where the roughness is difficult to control, the present invention not only improves the grinding efficiency, but also improves the finish and consistency of the final processed surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the processing steps of the present invention. DETAILED DESCRIPTION

[0021] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Embodiment 1: Please see attached Figure 1 The embodiment of the present invention provides a processing technology for a spiral grinding wheel, comprising the following steps: S1. Processing a substrate; the substrate is a light alloy material, and the light alloy material includes but is not limited to aluminum alloy, magnesium alloy, aluminum-magnesium alloy and alloy combinations thereof, and the substrate is turned to obtain a desired substrate shape.

[0023] Specifically, the spiral grinding wheel process of the present invention first starts with the processing of the substrate. The substrate uses a light alloy material, specifically including but not limited to aluminum alloy, magnesium alloy, aluminum-magnesium alloy and alloy combinations thereof. These materials have the advantages of light weight, high strength, corrosion resistance, etc., and are suitable for manufacturing a grinding wheel substrate that needs to withstand large cutting forces.

[0024] Turning is the core process of matrix forming. When aluminum alloy, magnesium alloy or aluminum-magnesium alloy is selected as the matrix material, the matrix first needs to be turned to obtain the required shape. Turning is a precision metal processing method that can ensure that the surface of the matrix is ​​flat and smooth, and can meet the required dimensional tolerance requirements.

[0025] During the turning process, CNC lathes are often used for precision control. The choice of turning tool depends on the type of alloy and the expected processing accuracy. Usually, the cutting speed of aluminum alloy is set to 3000rpm to 5000rpm to ensure processing efficiency while avoiding overheating. Magnesium alloys require a lower cutting speed (about 1500rpm to 3000rpm) to prevent overheating of the material or surface cracks. The turning depth is generally controlled between 1mm and 5mm. This range can ensure that the outer contour of the grinding wheel is accurately formed while maintaining the strength of the matrix structure.

[0026] This processing technology has the advantages of high precision and high efficiency, and can meet the manufacturing requirements of the spiral grinding wheel in the present invention. Through turning, the surface of the substrate is flattened, and the processing accuracy is guaranteed, especially in the bonding area between the substrate and the grinding strip. The high precision of turning can ensure the structural stability of the grinding wheel after bonding.

[0027] The lightweight alloy materials (aluminum alloy, magnesium alloy, aluminum-magnesium alloy) used in the present invention have multiple advantages: Lightweight: Compared with traditional steel or other alloys, aluminum alloy and magnesium alloy have lower density, which can effectively reduce the overall weight of spiral grinding wheel and reduce its burden in use. For high-speed applications, lightweight alloy materials can reduce the inertia of the grinding wheel and improve processing speed and accuracy.

[0028] High strength: Even lightweight alloy materials, aluminum alloys and magnesium alloys still have good strength. This ensures the stability of the grinding wheel during high-speed cutting and avoids the grinding wheel from breaking or deforming due to insufficient strength.

[0029] Good corrosion resistance: A dense oxide film is usually formed on the surface of aluminum alloy and magnesium alloy, which can effectively prevent corrosion and is particularly suitable for working in humid or chemically corrosive environments.

[0030] Excellent machinability: These alloy materials are easy to process such as turning, milling and drilling. Especially in the turning process, the excellent machining performance of the alloy materials can improve the machining efficiency and surface quality, reduce machining errors and ensure the accuracy of the matrix shape.

[0031] By using these light alloy materials, the stability and durability of the spiral grinding wheel of the present invention in the grinding process are improved. At the same time, the weight and inertia of the grinding wheel are reduced, so that the performance of the grinding wheel is better exerted under high speed and high load working conditions.

[0032] S2. Prepare resin material, please refer to Example 2-Example 4.

[0033] S3. Use a mold to extrude the superhard resin material to obtain grinding strips; the mold includes a mold plate and multiple cores installed inside. During the process, the superhard resin material is extruded through the cores to form grinding strips. The extrusion pressure is 0.5MPa to 2MPa, and the extrusion feed speed of the superhard resin material is 0.1mm / s to 0.5mm / s. After the superhard resin material in the mold is filled to the desired shape, it is naturally cooled for 1 to 2 hours.

[0034] Specifically, the mold used includes a mold plate and multiple cores, and the design and size of the cores are customized according to the shape, size and helix angle requirements of the required grinding bars. During the process, the resin superhard material is evenly squeezed into the mold, and through the action of the cores, a grinding bar with a predetermined helix angle and size is formed.

[0035] The extrusion pressure during the extrusion process is set to 0.5MPa to 2MPa. This pressure range can ensure that the superhard resin material fully fills the core space in the mold, and avoids bubbles and uneven distribution in the process, ensuring the consistency and stability of the grinding bar. This pressure level ensures the full flow of the resin material, so that it can completely fill the complex structure of the core, thereby forming a grinding bar with good density and uniformity. Too low pressure may cause insufficient or uneven material filling, affecting the performance of the grinding bar; while too high pressure may cause material loss or deformation of the core. Therefore, the range of 0.5MPa to 2MPa is the optimal control parameter selected by the present invention.

[0036] While the resin superhard material is being extruded, the extrusion feed speed is controlled between 0.1mm / s and 0.5mm / s. This feed speed ensures that the resin material can be evenly distributed in the core, avoiding uneven material distribution due to too fast feed or too slow feed causing a long processing cycle, which affects production efficiency. The appropriate feed speed can make the resin superhard material flow more evenly in the mold, thereby forming a high-precision grinding strip to meet the requirements of efficient grinding.

[0037] After extrusion, the superhard resin material in the mold needs to be naturally cooled for 1 to 2 hours. This cooling process is necessary to ensure that the resin material gradually solidifies and achieves the required structural stability. During this process, the temperature and shape of the material gradually stabilize, avoiding stress concentration or deformation caused by too fast cooling. The cooling time is selected within the range of 1 to 2 hours, which can effectively avoid cracks or deformation that may occur during the resin hardening process and ensure the quality and performance of the final grinding strip.

[0038] Through the above extrusion and cooling process, the final grinding bar has high consistency, good structural stability and excellent cutting performance.

[0039] S4. Bond the grinding strip to the substrate to form a complete spiral grinding wheel structure. The grinding strip is bonded using one or more epoxy resins or polyurethane adhesives. The bonding process uses a high temperature and high pressure curing method. The curing temperature is controlled at 50°C to 80°C, and the curing time is 1H to 2H.

[0040] Specifically, in order to stabilize the strong bond between the grinding strip and the substrate, epoxy resin or polyurethane adhesive is used. A single adhesive or a mixture of the two can be selected according to actual needs. The bonding process is carried out by high temperature and high pressure curing method, the curing temperature is controlled between 50℃ and 80℃, and the curing time is set to 1 hour to 2 hours to ensure the bonding strength and the overall stability of the grinding wheel.

[0041] Before bonding, select the appropriate adhesive according to the use environment and load of the grinding wheel. Epoxy resin is widely used in this type of bonding due to its excellent bonding strength and high temperature resistance. Polyurethane adhesive has advantages in certain specific applications due to its excellent flexibility and vibration resistance. For high-load, high-speed grinding environments, epoxy resin is usually used as the main adhesive. If higher impact and vibration resistance are required, polyurethane adhesive can be used, or the two adhesives can be mixed as needed to optimize the bonding effect.

[0042] Before bonding, the substrate and the grinding strip surface must be clean. Use appropriate solvents to clean the substrate and grinding strip surface to remove surface oil, dust and other impurities, and ensure that there is no material that hinders bonding on the bonding surface. This process can improve the adhesion of the adhesive and ensure a strong bond between the grinding strip and the substrate.

[0043] Apply the prepared adhesive evenly on the bonding surface of the grinding strip, ensuring that the adhesive coating thickness is uniform and free of bubbles. Then accurately align the grinding strip with the substrate, place it in the designated position, and gently apply pressure to fill the gap between the grinding strip and the substrate with the adhesive.

[0044] After the adhesive is applied, the grinding wheel will enter the high temperature and high pressure curing equipment. During the curing process, the temperature is controlled at 50℃ to 80℃, and the curing time is 1 hour to 2 hours to ensure that the adhesive can be fully cured and form a strong bond. In a high temperature environment, the curing speed of epoxy resin or polyurethane adhesive is accelerated, ensuring that a strong bond is completed in a short time.

[0045] Epoxy resin and polyurethane adhesives can be cured at high temperatures to improve their bond strength and heat resistance. High temperatures can also accelerate the cross-linking reaction of the adhesive to ensure the formation of a strong bond.

[0046] Use appropriate pressure (generally 1 to 3 MPa) during curing to ensure that the adhesive evenly fills the contact surface and avoids bubbling or uneven adhesive.

[0047] After curing, the grinding wheel needs to be cooled to room temperature. During the cooling process, maintain a stable ambient temperature to avoid stress concentration caused by rapid cooling. After cooling, the bond between the grinding strip and the substrate reaches the best strength, and the bonding area is firm and not loose. At this point, the grinding wheel can be processed and inspected.

[0048] The control parameters need to be designed according to the specific application scenario; The curing temperature is controlled between 50℃ and 80℃. Too high a temperature may cause the adhesive to decompose or cross-link excessively, affecting the bonding strength; while too low a temperature may result in incomplete curing and poor bonding. This temperature range ensures that the epoxy resin or polyurethane adhesive can be fully cured while maintaining sufficient strength and heat resistance.

[0049] The curing time is set to 1 to 2 hours, and the specific time depends on the type of adhesive, temperature and other conditions. Curing for too long will increase the production cycle, while curing for too short a time may result in insufficient bonding strength, so it needs to be optimized according to the specific situation.

[0050] The pressure applied during the curing process is usually between 1MPa and 3MPa and is controlled by hydraulic equipment. Appropriate pressure can ensure that the adhesive is evenly filled between the grinding strip and the substrate without causing deformation or adhesive overflow.

[0051] S5. Grind the outer side of the bonded grinding strip.

[0052] Specifically, in the spiral grinding wheel processing process of the present invention, the outer side of the bonded grinding strip is ground. This step is mainly used for sharpening, that is, improving the cutting ability of the grinding strip through fine grinding to ensure its high efficiency and precision in the actual grinding process. The goal of grinding is to make the outer side of the grinding strip have appropriate sharpness, optimize its cutting effect when it contacts the workpiece, and thus improve the overall grinding performance of the grinding wheel.

[0053] The helix angle during grinding has already been extruded and formed by the die, so there is no need to adjust or reprocess the helix angle in this step. The core of this process is to accurately adjust the shape of the outer side of the grinding bar by controlling the grinding angle, speed and abrasive. Specifically, the grinding feed rate is usually set between 0.1mm / s and 0.3mm / s to ensure that while maintaining accuracy, the grinding bar will not be damaged or uneven in shape due to over-grinding. The accuracy of the grinding angle is controlled within the range of ±0.05° to ±0.1° to ensure uniformity and consistency of the grinding wheel cutting.

[0054] Through this fine grinding process, the outer side of the grinding strip can obtain appropriate sharpness and uniformity, so that the grinding wheel can provide more stable cutting force during high-precision processing, avoiding the problem of unstable grinding caused by uneven outer side in traditional processes. In addition, the surface roughness of the grinding strip after grinding is controlled between Ra0.5 and Ra1.5, ensuring that the grinding wheel has good surface finish during high-speed grinding and reducing surface damage to the workpiece.

[0055] Embodiment 2: Recipe composition: Epoxy resin (bisphenol A type): 70%; Polyurethane resin (thermosetting polyurethane resin): 30%; Nano boron nitride (BN): 15%; Nano silicon carbide (SiC): 10%; Aluminum nitride (AlN): 8%; Surface enhancer (silane coupling agent): 2%; Preparation process steps: Step S21: Mix epoxy resin and polyurethane resin in a ratio of 70% and 30%. Use mechanical stirring to mix evenly, the stirring speed is set to 500 rpm, and the stirring time is 45 minutes. Ensure that the resin matrix is ​​fully uniform.

[0056] Step S22: Add nano boron nitride, nano silicon carbide and aluminum nitride into the resin matrix at a ratio of 15%, 10% and 8% respectively, and mix them using a high shear mixing device. The mixing time is 30 minutes to ensure that the fillers are fully dispersed and avoid any agglomeration.

[0057] Step S23: Add 2% of silane coupling agent and continue stirring for 10 minutes to ensure that the reinforcing agent and the resin matrix react completely to obtain a high-temperature fluid state resin material.

[0058] Step S24: Feed the resin material in a high-temperature fluid state into step S3 and extrude it using a mold with a feed speed of 0.3 mm / s and an extrusion pressure of 1.5 MPa to ensure that the resin material is evenly filled into the mold shape to complete the formation of the grinding strip.

[0059] Embodiment 3: Recipe composition: Epoxy resin (bisphenol A type): 65%; Polyurethane resin (thermosetting polyurethane resin): 35%; Nano boron nitride (BN): 12%; Nano silicon carbide (SiC): 7%; Aluminum nitride (AlN): 10%; Surface enhancer (titanate coupling agent): 1%; Preparation process steps: Step S21: Epoxy resin and polyurethane resin were mixed in a ratio of 65% and 35%. Mechanical stirring was used with the speed set at 350 rpm and the stirring time set at 30 minutes to ensure the uniformity of the resin matrix.

[0060] Step S22: Add nano boron nitride, nano silicon carbide and aluminum nitride into the resin matrix in proportions of 12%, 7% and 10%, and mix them using a high shear mixing device. The mixing time is set to 25 minutes.

[0061] Step S23: Add 1% titanate coupling agent and continue stirring for 12 minutes to ensure that the reinforcing agent and the resin matrix react fully.

[0062] Step S24: The high-temperature fluid resin material enters step S3 and is extruded using a mold with a feed rate of 0.2 mm / s and an extrusion pressure of 1.2 MPa. After being filled into the desired shape, it is naturally cooled for 1.5 hours to ensure the formation of the grinding strips.

[0063] Embodiment 4: Recipe composition: Epoxy resin (bisphenol A type): 75%; Polyurethane resin (thermosetting polyurethane resin): 25%; Nano boron nitride (BN): 18%; Nano silicon carbide (SiC): 6%; Aluminum nitride (AlN): 6%; Surface enhancer (silane coupling agent): 2%; Preparation process steps: Step S21: Epoxy resin and polyurethane resin are mixed in a ratio of 75% and 25%. Mechanical stirring is used with a stirring speed of 400 rpm and a stirring time of 50 minutes to ensure that the resin matrix is ​​uniform.

[0064] Step S22: Add nano boron nitride, nano silicon carbide and aluminum nitride into the resin matrix in a ratio of 18%, 6% and 6%, and mix using a high shear mixing device to ensure that the fillers are fully dispersed. The mixing time is set to 35 minutes.

[0065] Step S23: Add 2% of silane coupling agent and continue stirring for 12 minutes to ensure that the reinforcing agent reacts fully with the resin matrix.

[0066] Step S24: Feed the resin material into step S3, with a die extrusion feed speed of 0.4 mm / s and an extrusion pressure of 1.8 MPa. After filling into the desired shape, naturally cool for 1 hour to form a grinding strip.

[0067] Comparative Example 1: Recipe composition: Epoxy resin (bisphenol A type): 80%; Polyurethane resin (thermosetting polyurethane resin): 20%; Nano boron nitride (BN): 12%; Nano silicon carbide (SiC): 10%; Aluminum nitride (AlN): 8%; Surface enhancer (silane coupling agent): 2%; Preparation process: Step S21: epoxy resin and polyurethane resin are mixed in a ratio of 80% and 20%, and mechanically stirred at a speed of 400 rpm for 30 minutes.

[0068] Step S22: Add 12% nano boron nitride, 10% nano silicon carbide and 8% aluminum nitride, use high shear mixing equipment, and mix for 20 minutes.

[0069] Step S23: Add 2% of silane coupling agent and continue stirring for 10 minutes.

[0070] Step S24: die extrusion, feed rate 0.3 mm / s, extrusion pressure 1.0 MPa, cooling for 2 hours after filling.

[0071] Comparative description: This comparative example uses a slightly different ratio, in which the polyurethane resin ratio is reduced to 20%, and the content of nano boron nitride is 12%, which is reduced compared to 15% in Example 2. In the comparative experiment, the cooling time of the resin material is extended to 2 hours, which is longer than 1 to 2 hours in Example 1.

[0072] Comparative Example 2: Recipe composition: Epoxy resin (bisphenol A type): 68%; Polyurethane resin (thermosetting polyurethane resin): 32%; Nano boron nitride (BN): 14%; Nano silicon carbide (SiC): 8%; Aluminum nitride (AlN): 8%; Surface enhancer (titanate coupling agent): 1%; Preparation process: Step S21: epoxy resin and polyurethane resin are mixed in a ratio of 68% and 32%, and mechanical stirring is used. The stirring time is 30 minutes and the stirring speed is 400 rpm.

[0073] Step S22: Add 14% nano-boron nitride, 8% nano-silicon carbide and 8% aluminum nitride, and mix for 25 minutes.

[0074] Step S23: Add 1% of titanate coupling agent and continue stirring for 15 minutes.

[0075] Step S24: die extrusion, feed speed 0.25 mm / s, extrusion pressure 1.3 MPa, and natural cooling to solidification after filling.

[0076] Comparative description: The resin material of Comparative Example 2 uses different ratios of polyurethane resin and epoxy resin in the formula, and the ratio of nano boron nitride is 14%, which is increased compared to 12% in Example 3. This comparative example also selects a different surface enhancer (titanate coupling agent), resulting in the cooling time being set to natural cooling after curing, rather than natural cooling by timed cooling, which is different in the process steps.

[0077] Experimental design: In order to verify the advantages of the present invention in the application of spiral grinding wheels, the following experiments will be designed to compare the performance of the embodiment and the comparative example formulation under actual use conditions. The main test targets are wear resistance, high temperature resistance, bonding strength and service life to prove that the grinding strip resin material of the present invention can provide better comprehensive performance in a high-speed grinding environment.

[0078] Experiment 1: Wear resistance test Experiment purpose: To verify the difference in wear resistance of different formulations (example and comparative example) during long-term high-load grinding.

[0079] Experimental methods: Sample preparation: The spiral grinding wheel samples of Example 2, Comparative Example 1, Example 3 and Comparative Example 2 were selected, and 3 replicates of each sample were prepared.

[0080] Sample size: diameter 150mm, thickness 10mm, thickness of the grinding strip part is 5mm.

[0081] Grinding equipment: Using a standard grinding machine, a constant load grinding test was performed.

[0082] The grinding load was set to 30 N, the grinding speed was set to 25 m / s, and the grinding time was set to 10 hours.

[0083] Test steps: During the grinding process, the wear of the grinding bars is monitored and recorded.

[0084] The wear of the grinding bars was measured every 1 hour until the 10-hour grinding test was completed.

[0085] Data recording and analysis: Record the weight change of each sample grinding bar and calculate the wear amount.

[0086] The wear rates of the examples and comparative examples were compared to analyze the wear resistance of the different formulations.

[0087] Wear comparison data table: Sample No. Wear amount (g) Example 2 0.05 Comparative Example 1 0.12 Example 3 0.04 Comparative Example 2 0.11 From the experimental data, Example 3 has the best wear resistance and the smallest wear, indicating that the formula used in the present invention exhibits stronger wear resistance under high-load grinding conditions. The nano boron nitride and silicon carbide in the formula provide extremely high hardness and stability, especially in long-term high-speed grinding, the wear of the grinding bar is significantly lower than that of Comparative Examples 1 and 2. This shows that the formula design of the present invention optimizes the filler ratio while enhancing the hardness and wear resistance of the resin, thereby avoiding the problem of excessive wear.

[0088] The wear loss of Comparative Examples 1 and 2 is higher, which further verifies the negative impact of lower filler ratio on wear. Thus, appropriately increasing the proportion of nanofillers can effectively improve the performance of the grinding wheel during the grinding process.

[0089] Experiment 2: High temperature resistance test Experimental purpose: To verify the stability and thermal damage of different formulations in high temperature environment.

[0090] Experimental methods: Sample preparation: Comparative tests were performed using samples from Example 2 and Example 3 and Comparative Example 2 and Comparative Example 1, with 3 samples in each group.

[0091] The sample size and the thickness of the grinding bar section were the same and remained consistent with Experiment 1.

[0092] High temperature environment simulation: The samples were exposed to a high temperature environment at a temperature of 200°C to 300°C for testing.

[0093] A high temperature furnace is used to heat the sample to ensure that the sample surface reaches the set temperature range.

[0094] Test steps: Keep the samples in a high temperature environment for 24 hours at different temperatures.

[0095] Afterwards, take out the sample and observe and record the surface changes (such as cracks, softening, deformation, etc.).

[0096] Data recording and analysis: Record the changes in the sample's appearance and check for any thermal cracks or material softening.

[0097] Compare the performance of different formulations at high temperatures and evaluate their thermal stability.

[0098] Comparison table of crack quantity under high temperature environment: Sample No. Number of cracks Example 2 0 Comparative Example 1 3 Example 3 0 Comparative Example 2 2 Examples 2 and 3 showed significant thermal stability under high temperature environment, especially Example 2 had no cracks at all, which fully demonstrated the role of nano-boron nitride and aluminum nitride in improving the heat resistance of resin. The introduction of surface enhancer is a key factor in preventing thermal damage, which provides additional interface adhesion at high temperature and prevents the generation of cracks.

[0099] Relatively speaking, due to the insufficient filler ratio, the number of cracks in Comparative Example 1 increased significantly. This verifies the important role of fillers in the high temperature resistance of resin materials. The number of cracks in Comparative Example 2 is relatively large, especially at high temperatures, it is easy to soften, resulting in thermal damage to the material. Overall, the formula of the present invention has a significant advantage in high temperature stability, especially at extreme temperatures, its excellent thermal stability can better maintain the performance of the grinding wheel.

[0100] Experiment 3: Adhesion strength test Experimental purpose: To verify the bonding strength performance of different formulations in high-load and high-speed grinding.

[0101] Experimental methods: Sample preparation: The samples of Example 2, Comparative Example 1, Comparative Example 2 and Example 4 were used for comparison.

[0102] Sample specifications: diameter 150mm, thickness 10mm, thickness of the grinding strip part 5mm.

[0103] For each sample, the strips were bonded using either epoxy or polyurethane adhesive.

[0104] Bond strength test: After bonding is completed, the sample is placed in a tensile testing machine and a gradually increasing tensile force is applied until the bond line breaks.

[0105] The tensile force required to break was measured and the maximum tensile strength of each sample was recorded.

[0106] Test steps: After each sample is bonded, it is cured for 24 hours to ensure that the adhesive is fully cured.

[0107] During the test, the relationship between the tensile force and the sample deformation is recorded until the adhesive layer breaks.

[0108] Data recording and analysis: The maximum tensile strength of the samples of the embodiment and the comparative example were compared to evaluate the bonding strength of the different formulations.

[0109] By analyzing the results, the difference between the bonding performance of the formulation of the present invention and the prior art is evaluated.

[0110] Adhesion strength comparison data table: Sample No. Maximum tensile strength(N) Example 2 550 Comparative Example 1 350 Example 4 580 Comparative Example 2 400 Through the tensile test, it can be clearly seen that the bonding strength of Example 2 and Example 4 is significantly better than that of the comparative example sample. This shows that in the formulation of the present invention, the addition of the surface enhancer plays a key role in improving the bonding strength between the resin and the substrate.

[0111] The bonding strength of comparative example 1 is the worst, indicating that the low filler ratio leads to insufficient bonding performance of the resin matrix, and the bonding layer is prone to fall off during high-load grinding. The bonding strength of comparative example 2 is also low, indicating that the reasonable ratio of fillers is the key factor to ensure bonding strength.

[0112] Experiment 4: Lifespan test Experimental purpose: To verify the durability and service life of different formulations in long-term high-load grinding.

[0113] Experimental methods: Sample preparation: The samples of Example 2 and Example 3 and Comparative Example 1 and Comparative Example 2 were selected for comparison.

[0114] The sample is a spiral grinding wheel with a diameter of 150 mm and a thickness of 10 mm, and the thickness of the grinding strip is 5 mm.

[0115] Long-term grinding test: Long-term high-load grinding was carried out on the experimental equipment, with the grinding load set to 30N, the grinding speed to 30m / s, and the grinding time to 200 hours.

[0116] Test steps: During the grinding process, performance testing is carried out every 50 hours to check the wear of the grinding bars and whether the bonding layer has fallen off.

[0117] The samples were visually inspected every 100 hours and the morphological changes of the grinding bars were recorded.

[0118] Data recording and analysis: The total wear volume of each sample was recorded, and the surface condition after grinding was analyzed.

[0119] The service life of the examples and comparative examples was compared to evaluate the durability of the different formulations.

[0120] Service life comparison data table: Sample No. Total wear amount (g) Example 2 0.15 Comparative Example 1 0.25 Example 3 0.12 Comparative Example 2 0.28 The service life of Example 2 and Example 3 is significantly longer than that of the comparative sample, especially under long-term grinding, their wear amount is small. This shows that the formulation of the present invention significantly improves the durability of the grinding bar in long-term grinding through a reasonable filler ratio and resin ratio. In contrast, the wear amount of Comparative Example 1 and Comparative Example 2 is large, indicating that their durability is insufficient and the grinding bar is prone to large wear during high-speed grinding.

[0121] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A processing technology for a spiral grinding wheel, characterized in that: The following steps are involved: S1, processing the substrate; S2, preparing resin material; S3, using a mold to extrude the resin material to obtain a grinding strip; S4, bonding the grinding strip to the substrate to form a complete spiral grinding wheel structure; S5. Grind the outer side of the bonded grinding strip.

2. A processing technology for a spiral grinding wheel according to claim 1, characterized in that: The resin material in step S2 includes the following components: Epoxy resin: 60% to 80%; Polyurethane resin: 20% to 40%; Nano boron nitride: 10% to 20%; Nano silicon carbide: 5% to 15%; Aluminum nitride: 5% to 15%; Surface enhancer: 1% to 3%; Wherein, the surface enhancing agent includes a silane coupling agent or a titanate coupling agent.

3. A processing technology for a spiral grinding wheel according to claim 2, characterized in that: The epoxy resin is a bisphenol A epoxy resin with a molecular weight ranging from 400 to 600.

4. The processing technology of a spiral grinding wheel according to claim 2, characterized in that: The polyurethane resin is a thermosetting polyurethane resin, and its molecular weight ranges from 1000 to 3000.

5. The processing technology of a spiral grinding wheel according to claim 1, characterized in that: The preparation in step S2 includes: S21, mixing epoxy resin and polyurethane resin in a ratio of 60% to 80% and 20% to 40%, using mechanical stirring to evenly mix at a stirring speed of 300 rpm to 600 rpm, and continuing stirring for 30 minutes to 1 hour; S22, adding nano boron nitride, nano silicon carbide and aluminum nitride into the resin matrix in a ratio of 10% to 20%, 5% to 15% and 5% to 15%, respectively, and uniformly dispersing them by high shear mixing; S23, adding a surface enhancer in a ratio of 1% to 3%, and continuing stirring for 10 to 15 minutes to allow the enhancer to react with the resin matrix to obtain a high-temperature fluid state resin material; S24, the high temperature fluid state resin material enters step S3.

6. The processing technology of a spiral grinding wheel according to claim 1, characterized in that: In the step S1, the substrate is a light alloy material, and the light alloy material includes aluminum alloy, magnesium alloy, aluminum-magnesium alloy and alloy combinations thereof.

7. The processing technology of a spiral grinding wheel according to claim 1, characterized in that: In step S4, the grinding strips are bonded using one or more of epoxy resin or polyurethane adhesive.

8. The processing technology of a spiral grinding wheel according to claim 1, characterized in that: In the step S5, a grinding wheel is used to grind the outer side of the grinding strip, and the symmetrical grinding angle accuracy is controlled within ±0.05° to ±0.1°. The grinding feed speed is 0.1mm / s to 0.3mm / s, and the grinding wheel particle size is 60 mesh to 100 mesh.

9. The processing technology of a spiral grinding wheel according to claim 1, characterized in that: In the step S3, the extrusion feed speed of the resin material is 0.1 mm / s to 0.5 mm / s, and the extrusion pressure is 0.5 MPa to 2 MPa. After the resin material in the mold is filled into the desired shape, it is naturally cooled for 1 to 2 hours to obtain the desired grinding strip.

10. The processing technology of a spiral grinding wheel according to claim 1, characterized in that: In the step S4, the bonding is performed using a high temperature and high pressure curing method, the curing temperature is controlled at 50° C. to 80° C., and the curing time is 1 hour to 2 hours.

Citation Information

Patent Citations

  • Method for preparing ceramic bond diamond grinding wheel

    CN103586785A

  • Preparation method of composite binder superhard grinding wheel

    CN118848837A

  • Resinoid grinding wheel

    US20010000838A1